ANALISIS BIAYA PEMBIBITAN KELAPA SAWIT PT. REBINMAS JAYA, BELITUNG, BANGKA BELITUNG - Mulia, Ridho Rizky; Sayekti, Agatha Ayiek Sih; Nurjanah, Danik (Universitas Galuh, 2023)
The purpose of this research are; (1) to find out the oil palm nursery process at PT. Rebinmas Jaya; (2) for. know. How many. cost of oil palm nurseries, BEP (break event point), and sensitivity analysis at PT. Rebinmas Jaya; (3) to determine the cost efficiency of oil palm nurseries at PT. Rebinmas Jaya. The basic research method used is descriptive method. The data analysis used is cost volume profit and break event point. The results showed that the nursery at PT. Rebinmas Jaya uses a double stage system. The total cost of PT. Rebinmas Jaya in the amount of IDR 1,334,296,125 consisting of fixed costs of IDR 177,328,368 (13.4%) and variable costs of IDR 1,156,967,757 (86.6%). The unit break even point (BEP) is 10,859 and the rupiah BEP is IDR 434,360,000. Nursery PT. Rebinmas Jaya was declared feasible, with an R/C of 1.4. Comparative price efficiency of 66% is cheaper to do your own nursery compared to buying seeds from outside.